Scuba diving - Graver, Dennis (Champaign, IL : Human Kinetics, 2003)
Provides detailed instruction for scuba divers, presenting an introduction to the prerequisites, risks, and responsibilities of the sport, describing diving equipment, and covering the science behind diving, diving skills and adaptations, planning, the diving environment, and diving opportunities.
"Official scuba instructional manual of the YMCA of the USA"--Cover.
Includes bibliographical references (p. 203) and index.
Adult
Keywords: Scuba diving; Scuba diving